DISPARITAS PEMBANGUNAN EKONOMI ANTAR KABUPATEN/KOTA DI PROVINSI MALUKU (ANALISIS TIPOLOGI KLASSEN DAN INDEKS WILIAMSON) - Amin, Darwis (AMAL: Jurnal Ekonomi Syariah, 2019)
This study aims to determine the position of economic growth of each regency / city in Maluku Province based on economic growth and Gross Domestic Product (GDP) per capita and to determine the imbalance of economic growth between regencies / cities in Maluku Province. This research conduct with Klassen Typology analysis and Williamson’s Index analysis approach method. Research showed that regency/city that have significant growth in economic level percapita and gross domestic product (GDP) are Ambon City, and Tual City. Theregency/city that have minimal growth in economic level per capita and GDP are Maluku Tengah Regency, Buru Regency,Seram Bagian Barat Regency and Buru Selatan Regency. Disparity in economic development in Maluku Province is quite significant although income inequality in most regions is quite low because it has a relatively high level of economic growth and per capita income above the Maluku Province average.